Prediction of the cohesive crack growth in concrete beams in bending by mean of fracture mechanics and the finite element method - V., Tran Tu (Vietnam Journal of Mechanics, 1997)
The text presents the theoretical base for the construction of the program CGP-TROl. The fictitious crack model and the finite element method are employed for analyzing. This program is created to investigate two-dimensional models for the initiation and growth of the I-mode crack in notched beams in bending. The final result of the fracture analysis is the load-deflection diagram for the prediction of the cohesive crack growth in concrete notched beam in bending.